After-birth abortion: why should the baby live?. Issue 5 (23rd February 2012) - Giubilini, Alberto; Minerva, Francesca
Abstract : Abortion is largely accepted even for reasons that do not have anything to do with the fetus' health. By showing that (1) both fetuses and newborns do not have the same moral status as actual persons, (2) the fact that both are potential persons is morally irrelevant and (3) adoption is not always in the best interest of actual people, the authors argue that what we call 'after-birth abortion' (killing a newborn) should be permissible in all the cases where abortion is, including cases where the newborn is not disabled.